Cardiolipin acyl chain composition tailors the conformation of mammalian ATP synthase dimers - M. Makowski; V. G. Almendro-Vedia; I. López-Montero (Communications Chemistry)
Abstract The interplay between ATP synthase dimers and the four-tailed lipid cardiolipin (CL) shapes mitochondrial cristae structure and function. In the mitochondrial disorder Barth syndrome (BTHS), cristae membranes accumulate a less unsaturated, three-tailed form of cardiolipin (MLCL). These cristae become structurally and functionally compromised through mechanisms poorly understood. We have studied through molecular dynamics simulations how BTHS lipid composition affects the conformation of the ATP synthase dimer. The wedge-shaped transmembrane region of the ATP synthase dimer attracts cardiolipins through shape complementarity. MLCL showed decreased affinity for the dimer interface than CLs of the healthy model. A more heterogeneous lipid environment with a higher elastic strain promoted a dimer conformation that would stabilize wider intracrista spaces, and hence, less efficient OXPHOS reactions in BTHS. Our results provide clues on the role played by the CL acyl chain composition in the architecture and function of mitochondria in health and BTHS.